Default Judgment in the Draft Civil Procedural Code of the RA - Meghryan , S. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The institution of default judgment (proceedings in absentia) envisaged in the draft Civil Procedural Code of the Republic of Armenia is discussed in the article presented. The essence and key features of the judgment mentioned, its main advantages and the role in terms of reducing court load, optimization of hearings, settlement of civil cases and enhancing the efficiency of justice are analyzed. Based on doctrinal approaches on the peculiarities of considering cases in default judgment as well as analysis of transnational standards of civil procedure and foreign practice the author has conducted detailed study on the grounds of applying default judgment, the circumstances excluding consideration of cases in default judgment and the peculiarities of the procedural order of consideration and settlement of civil cases. Along with this, the article scrutinizes the procedural order of challenging the default judgment. Within the article the author has formulated and substantiated a range of suggestions and remarks aimed at amending default judgment. The conclusion is drawn up that the default judgment envisaged in the draft Civil Procedural Code of RA should be considered as successful and in line with transnational standards of settlement of cases through the mentioned institution. In the author’s opinion, it may facilitate the considerably reduction of the court load, elimination of time and financial expenses of persons involved in the case, expedient granting of judicial protection and realization of the most important tasks of litigation in general – procedural economy and optimization of consideration and settlement of civil cases.